The role of publicity and advertising in developing the financial resources of the professional football club in Algeria A field study on some football clubs of the First League - Moussaoui , Amel (sports creativity, 2025)
This study aims to underline and define the role that the propaganda and advertising technology acquires in the field of professional football in particular, and in the field of professional sports in general, as well as highlighting the relationship between sports and propaganda and advertising and defining it as a form of financing sports clubs under Sports Professionalism Project, and in our study the descriptive approach was used on a sample of7football teams for the First League, and the selection method was intentional and we used the questionnaire as a tool to collect information The most important results of the study indicated that publicity and advertising have an important role in developing the resources of the professional sports club. Accordingly, the clubs must try to apply the various fields of marketing that could bring them more financial revenues.